Micro-level dynamics of social assistance receipt. Evidence from 4 European countries - Sebastian Königs (Statistics Norway, Research Department, 2015)
This paper presents a study of the monthly dynamics of social assistance benefit receipt - in particular the distribution of spell lengths and the incidence of repeat receipt - in four European countries: Luxembourg, the Netherlands, Norway and Sweden. The analysis is based on four separate administrative panel data sets with long observation periods. Benefit dynamics vary considerably across countries over the eight-year period from January 2001 to December 2008: In the two Nordic countries, short-term benefit receipt is the norm with only around 6% and 11% of spells in Norway and Sweden lasting longer than 12 months. Most recipients however have multiple spells, and the majority of benefit leavers return to benefits within three months of leaving. In Luxembourg and the Netherlands, long-term benefit receipt is frequent, with median spell lengths of 14 and 9 months, respectively, and one-third and one-quarter of all spells lasting 24 months or longer. Benefit leavers in these countries are by contrast much less likely to return to benefit receipt after exit. The total duration of benefit receipt per individual across spells is two to three times as high in the Netherlands and Luxembourg than in Norway and Sweden over the eight-year period.
Keywords: I38; J60; 330; Social assistance dynamics; Welfare benefit dynamics; Benefit spell lengths